Solitary Cystic Mediastinal Lymphangioma: A Rare Incidental Case in an Adult Female - Aslam, Hira; Kamal, Anam; Khan, Ali Nauman; Chaudhary, Ahmed Jamal; Ismail, Rana (European Journal of Case Reports in Internal Medicine, 2022)
Introduction: Lymphangiomas are rare, congenital malformations arising from lymphatic hyperplasia. More than 90% of cases are found in children under 2 years of age. Cystic lymphangiomas usually occur in the neck and axillary region and only rarely extend to the mediastinum. Case Description: We present the case of a middle-aged woman who presented with dyspnoea and productive cough. A chest x-ray showed right lower medial lung opacity, and a CT scan of the thorax showed a cystic mediastinal mass, encroaching on the superior vena cava and approaching the trachea and mainstem bronchus. An anterior thoracotomy with tumour resection was performed to relieve compression symptoms. The final pathology report confirmed the diagnosis of mediastinal lymphangioma. Discussion: Lymphangioma should be considered as one of the differential diagnoses when mediastinal widening is found on chest x-ray, and it should be investigated further with a CT scan and biopsy. Infiltration of surrounding structures can cause compression symptoms and can also make surgical resection more challenging.